Agripreneurship Development: Breaking the Ice? - Gulsia, Oshin (AMC Indian Journal of Entrepreneurship, 2019)
Agriculture is the world’s largest sector and employs billions of people. It accounts for 3% of the global GDP. It offers a plethora of opportunities along the entire value chain. In nations in Asia and Africa, where industrialization is still in its infancy, agriculture is a predominant means of livelihood for the people. Globally, the current scenario is highly volatile due to various reasons like literacy, economic liberalization, better means of conveyance, and deregulation of agricultural markets. As such, the mainstream occupation of agriculture cannot fetch profitable returns unless it is synergized with entrepreneurship. Also, farmers of developing economies shirk away from adopting entrepreneurship as a means of improving their standard of living, thereby, reflecting a risk-aversive behavior, which is one of the major impediments to agripreneurship development. Against this backdrop, the present paper highlights the status of agripreneurship development with respect to several initiatives undertaken by the Government of India.